Care Support Education: Optimization Model of Communication Change Behavior in Female Sex Workers - Azinar, Muhammad; Fibriana, Arulita Ika; Matahari, Ratu; Nisa, Alfiana Ainun (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Female Sex Workers (FSW) are a group of populations at high risk of transmitting HIV/AIDS. In Indonesia, it is predicted that more than 50% of FSW suffer from sexually transmitted diseases (STDs), as well as in the district of Batang, Central Java, the most cases of HIV/AIDS in FSW. The main causes are weak sexual negotiation skills and economic reasons. The model of behavior change is the main key in decreasing cases of HIV/AIDS transmission. The Care Support Education (CSE) model is an innovative community-based behavior change communication. This research is pre experimental research with one group pretest posttest design. The population is FSW in Batang district localization totaling 123 people. Samples were taken by purposive sampling of 57 people. Test the effect of applying the CSE model on behavior change was analyzed using the Mc Nemar test. Condom use in risky sexual behavior among FSWs was still low (15.8%). Factors that influence it are knowledge, attitudes, perceptions of vulnerability, seriousness, benefits, negotiation capabilities and customer support. The application of the CSE model can significantly increase knowledge (p value 0.00006), attitude (0.0001), condom negotiation skills (0.000001) and practise of using condoms (0.000005).